Cucurbit Crops Acquired Silencing: Virus-Induced Post-Transcriptional Silencing Is Transmitted Across the Graft Union - Mei Ai; Wen Han; Zheng Wang; Xinyang Xu; Yanjun He; Weisong Shou; Xuepeng Sun; Huasen Wang; Jia Shen (Horticulturae)
Plant grafting is one of the oldest agricultural technologies, capable of improving biotic and abiotic stress resistance, regulating plant growth, and increasing crop output and quality. Recent analytical technology has revealed that massive numbers of RNAs can move via the phloem to regulate the gene expression in the scion. However, there are currently no high-throughput methods for validating the role of these long-distance RNAs in grafting, which limits the development of rootstock resources. In this study, methodologies were developed for infection of TRSV vectors in germinating melon seeds. Efficient infection was achieved in Védrantais with completely white first-true leaves and above. Grafting was performed after the gene silencing phenotype appeared in the rootstock, resulting in gene silencing of cucurbit crops as the scion. Furthermore, different RNA viral vectors were utilized to demonstrate that the transfer of viral vectors across the graft union induced gene silencing of the scion. The approach established in this study can provide a valuable research tool for future transfer RNA function studies and rootstock breeding.